(untitled) (American Journal of Education and Technology, 2024)
This study aims to determine whether water hyacinth can be a phytoremediation tool to mitigate eutrophication in water bodies. Specifically, it seeks to observe the morphological changes in the leaves and stems of water hyacinth in terms of length and width, to describe the similarities and differences of water hyacinth from eutrophic and normal water aquariums, and to determine the efficacy of water hyacinth in mitigating eutrophication. The research employed an experimental research design, which constitutes a structured set of protocols and procedures tailored for conducting experimental investigations scientifically, employing two distinct sets of variables. In conclusion, the study found significant changes in water hyacinth’s morphology when exposed to eutrophic water, with signs of distress observed after ten days due to high nutrient levels. Despite this, the findings support the potential of water hyacinth to mitigate eutrophication in water bodies, offering promise for enhanced water quality management.